Some of them with aspects of training students in surveyors student-centered individual training - KOCHERYGIN, Leonid (Journal of Education, Technology and Computer Science, 2013)
The article discusses some problems with the training of students, futureland surveyors, and creates educational opportunities for the development oftheir autonomy, community and accountability through student-oriented structureindividualized studying